Increasing Students’ Ability in Speaking through Film Conversation - Tianshy Ridwan; Jusriati Jusriati; Husnani Aliah (Universitas Muhammadiyah Enrekang, 2023)
This study aimed at finding out whether the use of Film Conversation can increase speaking ability. This study was conducted by using pre-experimental research. The population and the sample were the second grade students of SMAN 4 Palopo in 2022/2023 academic year. This research applied quantitative method. The analytical comparison result showed improvement using t-test. The output shows the average before and after the test (-25,640), standard deviation (10,222), mean standard error (2,044). The bottom difference (-29.859), while the top difference (-21,420). The result of the t test = (-23.983) with a df of 24 and a significance of 0,000. Mean score were higher after teaching using Film Conversation. This means that Ha is accepted and Ho is rejected. In conclusion, the use of Film Conversation is an effective strategy that is used to teach class XI of Senior High School Students.